Sexual dimorphism and geographic variation of Calotes versicolor (Squamata: Agamidae) in northern and southern Thailand - Prakobkarn, Arpapan; Thirakhupt, Kumthorn; Ngamprasertwong, Thongchai (Agriculture and Natural Resources, 2016)
The garden fence lizard, Calotes versicolor, is a common and widely distributed lizard throughout the Middle to Far-East including Indo-Asia and Thailand. Although this species displays variation in its morphology throughout its range, such variation has not been examined in Thailand. Thus, 20 adult lizards were examined from each of three geographically distinct populations in each of northern and southern Thailand to document any sexual and regional variation. Differentiation in characters between sexes and populations were tested using ANCOVA and principle component analysis for the mensural characters, the Mann-Whitney U-test for the meristic characters and the X2 test for coloration. Sexual dimorphism was found to occur in all populations. Males have a larger relative head size and longer relative limb lengths, whilst females exhibit a longer relative trunk length. The scalation of males was also more prominent than in females. Females in both the southern and northern Thailand populations have brighter patterns on the paired dorsolateral stripe, forearm stripe and paired nuchal spots than the corresponding males. Regional differentiation in mensural characters and coloration was more prominent in males, but no clustering of regional populations was found. Some meristic characters were congruent with regional variation. Males in the southern populations have a larger relative head size and longer relative limb lengths than those from the northern populations, but these differences were not found in females. Males in the southern populations have brighter patterns in dark bands on the trunk and colored throat patch than those in the northern populations.